Expression of a bacterial β-carotene hydroxylase in canthaxanthin producing mutant Mucor circinelloides strains - Csernetics, Árpád; Tóth, Eszter; Farkas, Anita; Nagy, Gábor; Bencsik, Ottó; Manikandan, Palanisamy; Vágvölgyi, Csaba; Papp, Tamás (Acta Biologica Szegediensis, 2014)
Xanthophylls, primarily hydroxyl- and keto-derivatives of β-carotene (such as zeaxanthin, β-cryptoxanthin, canthaxanthin, echinenone and astaxanthin) have powerful antioxidant activity. Due to several positive effects on human and animal health, industrial application of xanthophylls shows an increasing tendency. In our previous study, carotenoid biosynthesis of the β-carotene producing zygomycetes, Mucor circinelloides was modified by integrating the β-carotene ketolase encoding gene (crtW) of Paracoccus sp. N81106 into the genome. The isolated mutants accumulated mainly canthaxanthin and echinenone. Although, the fungus has β-carotene hydroxylase activity the astaxanthin production remained low even under different cultivation conditions, whereby canthaxanthin accumulation was further enhanced. In this study, the β-carotene hydroxylase encoding gene (crtZ) of the same bacterium was introduced into these canthaxanthin producing mutants of M. circinelloides either on autonomously replicating plasmids or by integrating it into the genome using the REMI method. Increased astaxanthin accumulation was observed in the transformants, which together with zeaxanthin and β-cryptoxanthin content could be further enhanced several fold by the modification of the cultivation conditions. An effective method for the extraction of carotenoids from Mucor mycelia grown in liquid culture was also developed.